2011
DOI: 10.1007/s11273-011-9214-6
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions and carbon sequestration potential in restored wetlands of the Canadian prairie pothole region

Abstract: North American prairie pothole wetlands are known to be important carbon stores. As a result there is interest in using wetland restoration and conservation programs to mitigate the effects of increasing greenhouse gas concentration in the atmosphere. However, the same conditions which cause these systems to accumulate organic carbon also produce the conditions under which methanogenesis can occur. As a result prairie pothole wetlands are potential hotspots for methane emissions. We examined change in soil org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
118
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 39 publications
10
118
1
Order By: Relevance
“…As data have become available and coarse-scale models refined, a variety of studies have recognized the contribution of inland aquatic ecosystems (e.g., wetlands, peatlands, reservoirs) to the terrestrial carbon budget (Armentano and Menges, 1986;Gorham, 1991;Algesten et al, 2003;Bridgham et al, 2006Bridgham et al, , 2013Cole et al, 2007;Downing et al, 2008;Battin et al, 2009). Despite this, soil organic carbon (OC) and greenhouse gas (GHG) flux data characterizing wetland ecosystems are relatively sparse, often region-or classificationspecific, and associated with a high degree of uncertainty (Bridgham et al, 2006(Bridgham et al, , 2013Euliss et al, 2006;CCSP, 2007;Phillips and Beeri, 2008;Gleason et al, 2009;Badiou et al, 2011;Pennock et al, 2010;Finocchiaro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As data have become available and coarse-scale models refined, a variety of studies have recognized the contribution of inland aquatic ecosystems (e.g., wetlands, peatlands, reservoirs) to the terrestrial carbon budget (Armentano and Menges, 1986;Gorham, 1991;Algesten et al, 2003;Bridgham et al, 2006Bridgham et al, , 2013Cole et al, 2007;Downing et al, 2008;Battin et al, 2009). Despite this, soil organic carbon (OC) and greenhouse gas (GHG) flux data characterizing wetland ecosystems are relatively sparse, often region-or classificationspecific, and associated with a high degree of uncertainty (Bridgham et al, 2006(Bridgham et al, , 2013Euliss et al, 2006;CCSP, 2007;Phillips and Beeri, 2008;Gleason et al, 2009;Badiou et al, 2011;Pennock et al, 2010;Finocchiaro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1) covers approximately 821,859 km 2 and includes portions of five U.S. states and three Canadian provinces . The PPR is characterized by relatively small (often b5 ha), highly productive, mineral-soil wetlands dispersed throughout an agriculture-dominated landscape, and prairie pothole wetlands have potential to be important ecosystems in terms of the North American carbon balance (Bridgham et al, 2006;Euliss et al, 2006;Badiou et al, 2011). Studies from North America, including the PPR, have shown that minimally disturbed wetland catchments in native grasslands have relatively high soil OC levels, and soils of wetland catchments in an agricultural setting are capable of sequestering OC when restored to a similar natural state (Follett et al, 2001;Desjardins et al, 2005;Euliss et al, 2006;Gleason et al, 2008Gleason et al, , 2011Badiou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration or creation may be justified in estuarine wetlands where low methane emissions and enhanced sequestration lower net radiative forcing. In freshwater wetlands, outcomes are uncertain; restoration or creation may increase net radiative forcing with increased methane emissions (Bridgham et al 2006) or may have the potential to become net radiative sinks (Badiou et al 2011;Mitsch et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most notable programs include the U.S. Department of Agriculture Cropland Reserve Program (CRP) and Wetlands Reserve Program (WRP), the U.S. Fish and Wildlife Service Partners for the Fish and Wildlife Program, and land protection programs of Ducks Unlimited Inc., a non-governmental organization (Badiou et al 2011; USDA Natural Resources Conservation Service 2012). Particular to the Great Plains, DU has partnered in its easement program with the Plains Carbon Dioxide Reduction (PCO 2 R) Partnership, a collaboration of over 80 U.S. and Canada stakeholders to protect 10,643 ha of native grassland in the prairie pothole region under perpetual conservation easements that will be donated to the U.S.…”
Section: Introductionmentioning
confidence: 99%